Consumers', Family Members', and Health Practitioners' Perspectives on Increasing Activity Engagement of Older Patients Admitted to Geriatric Hospital Units - Yvonne Y.K. Mak-Yuen; Farnaz Khoshmanesh; Tamara Tse (Patient Experience Journal)
The aim of this study was to explore the perspective of consumers, family members, and health practitioners on increasing patient activity engagement in a Geriatric Evaluation and Management (GEM) Unit. This study followed a qualitative phenomenology approach. Semi-structured interviews were conducted, audio-recorded and transcribed verbatim with consenting patients (n = 12), family members (n = 3), and health practitioners (n = 5) admitted to the GEM Unit of a tertiary metropolitan hospital in Melbourne, Victoria, Australia between August 2017 and March 2018. Data were analysed using spiral content analysis. From the 20 interviews, three themes emerged: 1. What can I do, 2. What I want to do, and 3. What can we do? Patients received limited opportunities to be active during hospitalisation. They were often faced with nothing to do and unsure what to do. Patients frequently reported higher activity levels at home. Activities that were enjoyable, beneficial, and of their own choice drove their desire to engage. Family members and health practitioners played an essential role in facilitating patients' engagement and required knowledge and skills to do so. Other Australian hospitals have used environmental enrichment strategies to increase patients' activity. Implementing such strategies, including tailored individual and communal activities to increase activity participation should align with patients' preferences and needs.